“Where Barley is Kept, Rye Cannot Fit in”: The Pathways of One Proverb - Kudirkienė, Lilija (Tautosakos darbai, 2015)
The proverb ‘Where barley is kept, rye cannot fit in’ (Kur miežiai guli, rugiai netelpa), or its variant ‘Where barley is stored / kept, no rye is necessary’ (Kur miežiai telpa / guli, nereik rugių), which means that those who drink do not usually eat much, did not have oral tradition in Lithuania, being spread via publications instead. It belongs to an international type. The Lithuanian text, although written down by Jokūbas Brodovskis (1692–1744) in the first half of the 18th century, became publicly known only since the beginning of the 19th century, along with the dictionary compiled by Christian Gottlieb Mielcke (1800). Later this proverb made its appearance in works by Józef Ignacy Kraszewski (1847), Georg Heinrich Ferdinand Nesselmann (1851), and Friedrich Becker (1866). It reached the American Lithuanians in 1904 thanks to Jonas Šliūpas. In Lithuania, this proverb started its dissemination with the Lithuanian reader compiled by August Schleicher (1857), in which two variants of this proverb were printed: one copied from the manuscript dictionary of J. Brodovskis, while another one recorded by A. Schleicher himself in the Lithuania Minor. From this reader, the proverb was reprinted in the dictionary by Mykolas Miežinis (1894) and found its way into the collections of the Lithuanian Science Society, thus being spread wider. Vincas Krėvė published it in Tauta ir žodis (‘Nation and Word’, 1927). Both variants of this proverb were included into the anthology Lietuvių tautosaka (‘Lithuanian Folklore’, vol. 5, 1968).In the second half of the 18th century, a very similar variant of this proverb appeared also in Latvian. It was published in the grammar book by Gotthard Friedrich Stender in 1761: Kur miežu grauds guļ, tur rudzu grauds nevar gulēt (‘Where a barley grain lies, no grain of rye should lie’). In the 19th century, it also found its way into various collections of Latvian folklore, both printed and manuscript ones. Nevertheless, according to the researchers, the oral tradition of this proverb is absent in Latvia as well.It is almost certain that original source of this proverb should have been in German. Still, the German tradition prefers versions with opposition between brewery / distillery and bakery (Brauhaus – Backhaus) rather than between barley and rye. According to various researchers, the German publications containing opposition between grains of barley and rye were mostly published in the 19th century, i.e. considerably later than authors recording the Lithuanian and Latvian versions lived. On the other hand, earlier German publications available to us now are very old (published in 1606 in Hamburg or 1616 in Augsburg) and could have hardly been traceable to the authors of the 18th century sources mentioned above. Therefore the text noted down by J. Brodovskis could have originated not from a published source, but from a spoken German in the Prussian territory. The origins of the Latvian analogue seem even more enigmatic, though. The German speaking area is separated from Latvia by the Lithuanian territory. Could Latvians have picked this proverb from the Baltic Germans? The direct link between the Lithuanian and Latvian versions is difficult to establish. There is a slight possibility that the Latvian version (or perhaps the Lithuanian one as well?) could have originated from an unknown printed German source. Otherwise the similarity of the Lithuanian and Latvian versions can only be regarded as a coincidence.
Keywords: -